The Effect of Product Quality and Service Quality on Loyalty with Customer Satisfaction as A Mediation Variable (A Study at Wizzmie Jimbaran Restaurant) - Nelson Pally (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to determine and analyze the effect of product quality and service quality on loyalty, with customer satisfaction as a mediating variable. This study was conducted at the Wizzmie Jimbaran Restaurant in Badung Regency. The sample size was 95 people. Data collection was conducted using questionnaires. The data analysis technique used was SEM-PLS. The results of this study indicate that product quality, service quality, and customer satisfaction have a positive and significant effect on loyalty. Product quality and service quality have a positive and significant effect on customer satisfaction. Customer satisfaction can mediate the effect of product quality and service quality on loyalty. The results of this study can provide an overview for management that increasing loyalty depends not only on product quality but also on the quality of service provided to customers.